If I could turn back time - Harbison, Elizabeth M. (St. Martin's Press, 2015)
On a boat with friends off the Florida coast, Ramie Phillips tries to fight her feelings of discontent with steel will and hard liquor. No one even notices as she gets up and goes to the diving board and dives off... and wakes up almost twenty years in the past, at home in bed with her mother waking her up for school. With a second chance to see the people she's lost and change the choices she regrets, Ramie will have to answer the question that no one else can: What it is that she really wants from the past, and for her future?